Effects on platelet function of an EP3 receptor antagonist used alone and in combination with a P2Y12 antagonist both in-vitro and ex-vivo in human volunteers. (August 2013) - Fox, S.C.; May, J.A.; Johnson, A.; Hermann, D.; Strieter, D.; Hartman, D.; Heptinstall, S.
<x xml:space="preserve">Abstract</x> EP3 receptor antagonists may provide a new approach to the treatment of atherothrombotic disease by blocking the ability of prostaglandin E2 (PGE2) to promote platelet function acting via EP3 receptors. DG-041 is an EP3 antagonist in the early stage of clinical development. Here, we quantitated effects on platelet function of DG-041 in-vitro and ex-vivo after administration to man when given alone and concomitantly with clopidogrel or clopidogrel and aspirin. With its unique mechanism of action, it was anticipated that DG-041 would potentiate inhibition of platelet function when given in combination with clopidogrel without materially increasing bleeding time. Initially, in-vitro studies were performed to determine inhibitory effects of DG-041 (3 µM) used alone or in combination with the P2Y12 antagonist cangrelor (1 µM), both without and with aspirin (100 µM). Platelet aggregation and P-selectin expression were measured in whole blood (n = 10) following stimulation with the thromboxane A2 (TXA2) mimetic U46619 (0.3 or 1 µM) in combination with either the EP3 agonist sulprostone (0.1 µM), or PGE2 (1 µM). DG-041 alone partially inhibited platelet function in-vitro, as did cangrelor. Addition of both DG-041 and cangrelor in combination provided significantly greater inhibition. An ex-vivo study was then performed using the same experimental approaches. This clinical study was a prospective, randomised, blinded (for DG-041/matching placebo), blocked, crossover study designed to compare the effects of DG-041, clopidogrel, or the combination of DG-041 with either clopidogrel or clopidogrel and aspirin. Healthy volunteers (n = 42) were randomly assigned to receive no background treatment, clopidogrel (300 mg loading dose plus 75 mg daily) or clopidogrel and aspirin (75 mg daily) for 10 days alongside DG-041 (200 mg twice daily) or placebo for 5 days, crossed over to placebo or DG-041 for the next 5 days. Platelet effects and bleeding time were measured at baseline, days 5 and 10. DG-041 partially inhibited platelet function ex-vivo, as did clopidogrel, while administration of both DG-041 and clopidogrel provided significantly greater inhibition. Administration of DG-041 alone did not increase bleeding time, and did not significantly affect the increased bleeding time seen with clopidogrel or clopidogrel with aspirin. Using these experimental approaches, the antiplatelet effects of DG-041 and a P2Y12 antagonist used alone and in combination can be determined both in-vitro and ex-vivo. Results show inhibitory effects of DG-041 on platelet function acting via EP3 receptor blockade, confirmed to be additional to those brought about by P2Y12 blockade. In both in-vitro and ex-vivo studies, aspirin neither promoted nor negated the effects of the other drugs.